Efficacy of Proanthocyanidins in Nonsurgical Periodontal Therapy - Evelina Alkimavičienė; Rasa Pušinskaitė; Nomeda Basevičienė; Rasa Banienė; Nijolė Savickienė; Ingrida Marija Pacauskienė (Elsevier, 2023)
Background: The aim of this work was to evaluate the efficacy of proanthocyanidins (PACNs) as an adjunctive periodontal therapy in patients with periodontitis. Methods: Patients with periodontitis (stage III-IV) were included in this randomised clinical study. Patients with periodontitis received 2 different treatment modalities: minimally invasive nonsurgical therapy only (MINST group) or minimally invasive nonsurgical therapy and subgingival application of collagen hydrogels with PACNs (MINST + PACNs group). Clinical periodontal parameters, that is, pocket probing depth (PPD), clinical attachment level (CAL), bleeding on probing (BOP), plaque index (PI), were evaluated before treatment and after 8 weeks. Concentrations of immunologic markers, matrix metalloproteinase-3 (MMP-3), and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) in saliva were assessed at baseline and at 8-week follow-up. Results: Forty-six patients diagnosed with periodontitis were randomised into 2 groups: 23 patients in the MINST group and 23 patients in the MINST + PACNs group received the intended treatment. PACNs combined with MINST resulted in additional statistically significant PPD reduction and CAL gain in moderate periodontal pockets by 0.5 mm (P < .05) on average compared to MINST alone. Additional use of PACNs did not result in additional statistically significant improvement of BOP or PI values. Application of PACNs showed significant reduction of MMP-3 levels in saliva after 8 weeks (P < .05). Conclusions: Adjunctive use of PACNs in MINST resulted in better clinical outcomes for moderate pockets. Additional use of PACNs improved MMP-3 concentration in saliva more than MINST alone. Biochemical analysis revealed that MMP-3 concentration in saliva reflected the periodontal health state.